El aprendizaje mediado por la tecnología: Una estrategia para fortalecer la autoestima de los estudiantes de los grados 9, 10 y 11 en los entornos de trabajo remoto. (2021)
This work is carried out in order to know the perception of students in grades 9, 10 and 11 of two (2) Educational Institutions of the City of Bogotá (one private and the other public), in relation to their self-esteem and learning in mediated environments by technology, to design a strategy that helps reduce the risk factors that affect these two (2) aspects in students